2013
DOI: 10.1093/nar/gkt563
|View full text |Cite
|
Sign up to set email alerts
|

The eIF2α/ATF4 pathway is essential for stress-induced autophagy gene expression

Abstract: In response to different environmental stresses, eIF2α phosphorylation represses global translation coincident with preferential translation of ATF4, a master regulator controlling the transcription of key genes essential for adaptative functions. Here, we establish that the eIF2α/ATF4 pathway directs an autophagy gene transcriptional program in response to amino acid starvation or endoplasmic reticulum stress. The eIF2α-kinases GCN2 and PERK and the transcription factors ATF4 and CHOP are also required to inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
727
4
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 889 publications
(800 citation statements)
references
References 67 publications
25
727
4
3
Order By: Relevance
“…[33][34][35][36][37] In this regard, recent studies have identified DDIT3 as a direct regulator of numerous genes involved in the autophagic process. [38][39][40] Here, we show that the increase of transcripts levels of several autophagy-and lysosome-related genes in colchicinetreated fish paralleled that of Ddit3 mRNA supporting these previous studies. However, the increase of lysosomal transcripts was not followed by an increase of the lysosomal function (as evidenced by the activity of CTSD), in line with the demonstrated inhibition of the autophagic flux in our samples and the recently published data showing that activation of lysosomal function depends on autophagosome-lysosome fusion.…”
Section: Discussionsupporting
confidence: 90%
“…[33][34][35][36][37] In this regard, recent studies have identified DDIT3 as a direct regulator of numerous genes involved in the autophagic process. [38][39][40] Here, we show that the increase of transcripts levels of several autophagy-and lysosome-related genes in colchicinetreated fish paralleled that of Ddit3 mRNA supporting these previous studies. However, the increase of lysosomal transcripts was not followed by an increase of the lysosomal function (as evidenced by the activity of CTSD), in line with the demonstrated inhibition of the autophagic flux in our samples and the recently published data showing that activation of lysosomal function depends on autophagosome-lysosome fusion.…”
Section: Discussionsupporting
confidence: 90%
“…86 In addition, underscoring the complexity of this interplay, NFE2L2 controls the expression of the autophagy cargo receptor SQSTM1, but at the same time, phosphorylated SQSTM1 partly controls the activity of NFE2L2 by sequestering its negative regulator KEAP1. 58,64-66 NFE2L2 transcriptionally cooperates with several cellular stress response pathways, including ATF4-regulated stress responses, 87 that further regulates SQSTM1, 88 and autophagy. 89 Also, in addition to TFEB (transcription factor EB), 90 recent studies have pointed to CREB (cAMP responsive element binding protein) and PPARA (peroxisome proliferator-activated receptor a) important for the transcriptional regulation of autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…How are only the proteins related to the elongation step of autophagosome formation suppressed by heat stress? Unlike other ATGs, ATG5-12 conjugate and ATG16L were suggested to be regulated by the activating transcription factor 4 (ATF4) from a previous study 46) and databases. It is known that ATF4 is activated by increased endoplasmic reticulum (ER) stress.…”
Section: Heat Stress Attenuates Denervation-activated Mitophagic Fluxmentioning
confidence: 97%